2020
DOI: 10.1177/1075547020959818
|View full text |Cite
|
Sign up to set email alerts
|

A Metacognitive Approach to Reconsidering Risk Perceptions and Uncertainty: Understand Information Seeking During COVID-19

Abstract: The study examined the psychological drivers of information-seeking behaviors during the coronavirus disease 2019 (COVID-19) outbreak. Employing a two-wave (from April 16, 2020, to April 27, 2020) survey design ( N = 381), the study confirmed that both risk perceptions and uncertainty were important antecedents to information seeking and that their effects were linked to emotional appraisals of the risk situation. Findings revealed nuanced relationships between these two constructs and emotional appraisals. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 75 publications
(151 reference statements)
2
37
0
1
Order By: Relevance
“…AYAs struggled to understand this risk and how the varying guidelines in response to the pandemic (e.g., quarantining) would impact or change risk. While unknown risk is not unique to AYA cancer patients and survivors [ 19 , 20 ], the unclear risk perception among AYAs created additional stress around medical decision-making. At times, for example, it was not clear to AYAs whether it was safer to postpone treatment or surveillance care and risk possible recurrence or to attend scheduled appointments when they were available and risk potential COVID-19 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…AYAs struggled to understand this risk and how the varying guidelines in response to the pandemic (e.g., quarantining) would impact or change risk. While unknown risk is not unique to AYA cancer patients and survivors [ 19 , 20 ], the unclear risk perception among AYAs created additional stress around medical decision-making. At times, for example, it was not clear to AYAs whether it was safer to postpone treatment or surveillance care and risk possible recurrence or to attend scheduled appointments when they were available and risk potential COVID-19 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…These studies found that during the initial phases of the SARS outbreak, risk perception steadily increased and then leveled off in later phases [ 21 , 31 ]. As explained by other studies of public risk perception, the risk associated with COVID-19 was novel and poorly known, disrupting the safety system of people’s cognitions, which was reflected by an explosion in information seeking [ 32 ]. However, as an infectious disease, the increase in risk perception could be neutralized by effective vaccines or behavioral containment measures, which would likely lead to less concern regarding the notion of risk.…”
Section: Discussionmentioning
confidence: 99%
“…Nan et al (2018) proposed an integrative framework that called special attention to the mode of information processing. Guided by this framework, psychological uncertainty, a concept centering around information experience (Huang & Yang, 2020), may be particularly relevant to understanding how individuals process framed messages promoting COVID-19 vaccination.…”
Section: Moderating Effects Of Psychological Uncertaintymentioning
confidence: 99%